2022
DOI: 10.1002/acm2.13520
|View full text |Cite
|
Sign up to set email alerts
|

Safety of magnetic resonance imaging in patients with cardiac implantable electronic devices with generator and lead(s) brand mismatch

Abstract: Magnetic resonance imaging (MRI) is a valuable imaging modality for the assessment of both cardiac and non‐cardiac structures. With a growing population of patients with cardiovascular implantable electronic devices (CIEDs), 50%–75% of these patients will need an MRI. MRI‐conditional CIEDs have demonstrated safety of MRI scanning with such devices, yet non‐conditional devices such as hybrid CIEDs which have generator and lead brand mismatch may pose a safety risk. In this retrospective study, we examined the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The CIED system as a whole, even if individual components are classified as MR-conditional, may fall outside of labeling if the patients have mismatched CIED-lead vendors. As shown in Table 1 , a combined prospective/retrospective study with 246 generator models, 210 lead models and 638 unique generator-lead combinations published by Bhuva et al reported no increased risk of MRI in patients with mismatched device-lead vendors compared to those with matched vendors [35] ; this study was consistent with a smaller previous study [36] . While these two initial studies are encouraging, it should be noted that they do not cover all potential combinations/permutations of such mismatches.…”
Section: Up-to-date Evidence On Mr Safety and Scmr-endorsed Recommend...supporting
confidence: 86%
“…The CIED system as a whole, even if individual components are classified as MR-conditional, may fall outside of labeling if the patients have mismatched CIED-lead vendors. As shown in Table 1 , a combined prospective/retrospective study with 246 generator models, 210 lead models and 638 unique generator-lead combinations published by Bhuva et al reported no increased risk of MRI in patients with mismatched device-lead vendors compared to those with matched vendors [35] ; this study was consistent with a smaller previous study [36] . While these two initial studies are encouraging, it should be noted that they do not cover all potential combinations/permutations of such mismatches.…”
Section: Up-to-date Evidence On Mr Safety and Scmr-endorsed Recommend...supporting
confidence: 86%
“…26 , 27 , 28 For limitations related to CIEDs, recent studies demonstrate that CMR in non-MRI-conditional systems, including those with hybrid configurations, is feasible and safe without clinically meaningful device parameter changes or adverse events. 29 , 30 Though, abandoned leads remain a challenge. 31 , 32 , 33 , 34 Recent advances in wideband LGE protocols, for both segmented and single-shot sequences, have demonstrated efficacy in accurately reducing device-related artifact, particularly with transvenous ICDs and cardiac resynchronization therapy devices.…”
Section: Discussionmentioning
confidence: 99%